The equation to model the situation is
![=71-t * (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ggswhlm0zducv9g0kozl12qhmar3l9svnh.png)
Solution:
Given, Grandpa Joe started getting shorter in 2002 (let x=0)
Height shrunken =
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
Present Height in 2008 = 68 inches
Now, let the number of years lived after 2002 be “t”
Then, present height = height in 2002 – number of years lived x height shrunken
![\text { Present height }=\text { height in } 2002-t * (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ksllhk3qyqsdwb56gkqtdrf4hljldwpluy.png)
Since from 2002 to 2008 , it is 6 years span, so t = 6
![\text { Present height in } 2008=\text { height in } 2002-6 * (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w4zqv1ocgvaxchhoo4oifzgu28sqaubdkj.png)
68 inches = height in 2002 – 3 inches
Height in 2002 = 68 + 3 = 71 inches
So, grandpa is 71 inches tall in 2002
Then, our equation will be modified as present height
![=71-t * (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ggswhlm0zducv9g0kozl12qhmar3l9svnh.png)